Seroepidemiological study of interepidemic Rift Valley fever virus infection among persons with intense ruminant exposure in Madagascar and Kenya - Gray, G.C (American Society of Tropical Medicine and Hygiene, 2020)
10.4269/ajtmh.15-0383